2020
DOI: 10.3389/fpsyg.2020.579181
|View full text |Cite
|
Sign up to set email alerts
|

Safe but Lonely? Loneliness, Anxiety, and Depression Symptoms and COVID-19

Abstract: BackgroundThe COVID-19 pandemic has led governments worldwide to implement unprecedented response strategies. While crucial to limiting the spread of the virus, “social distancing” may lead to severe psychological consequences, especially in lonely individuals.MethodsWe used cross-sectional (n = 380) and longitudinal (n = 74) designs to investigate the links between loneliness, anxiety, and depression symptoms (ADS) and COVID-19 risk perception and affective response in young adults who implemented social dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
93
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(138 citation statements)
references
References 62 publications
11
93
0
5
Order By: Relevance
“…Specifically, this was more evident within the younger population. Moreover, Okruszek et al ( 2020 ) and Killgore et al ( 2020 ) found the social isolation measures implemented during the pandemic predicted increased loneliness, depressive and anxiety symptoms. Our results show Serene can reduce feelings of isolation and depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, this was more evident within the younger population. Moreover, Okruszek et al ( 2020 ) and Killgore et al ( 2020 ) found the social isolation measures implemented during the pandemic predicted increased loneliness, depressive and anxiety symptoms. Our results show Serene can reduce feelings of isolation and depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to these specific sources of stress, a study by Okruszek et al (2020) with Polish young adults found that the COVID-19 risk perception (e.g., contact risk, severe symptoms risk, and financial problem risk) and the feeling of loneliness led to affective responses to the situation during the first 2 weeks of the crisis. However, it is also interesting to note that some individual stressors, such as work overload, strict schedules, Fears of Missing Out on social life (FoMO) or competition among students might in fact have been mitigated during the crisis situation for some students ( Elmer et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Loneliness has been defined as the embodiment of social isolation and can show an individual's negative feelings about the frequency and closeness of their social contacts (Steptoe et al, 2013 ). In addition, loneliness has been associated with increased levels of depressive symptoms (Cacioppo et al, 2006 ; Matthews et al, 2016 ; Palgi et al, 2020 ; Rosenberg et al, 2020 ), increased symptoms of anxiety (Ernst and Cacioppo, 1999 ; Cacioppo et al, 2006 ; Okruszek et al, 2020 ; Palgi et al, 2020 ), and an altered mood state (Loucks, 1980 ; Besser et al, 2020 ). Prolonged time at home, loneliness (Page and Hammermeister, 1995 ; Hawkley et al, 2009 ; Richard et al, 2017 ; Schrempft et al, 2019 ; Creese et al, 2020 ), and mental health disturbances (Mayou et al, 2000 ; Brummett et al, 2003 ; Stewart et al, 2003 ; Van Gool et al, 2003 ; Allan et al, 2007 ; Da Silva et al, 2012 ; Legey et al, 2017 ; Stubbs et al, 2017 ; Creese et al, 2020 ; López-Bueno et al, 2020 ; Stanton et al, 2020 ) can increase behaviors that promote sedentary behavior and decrease overall physical activity (Biddle, 2016 ; Creese et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%